(3OjhGf GHf Sgd GdESQGFjdis - (3GHf Sgd , CHh ESMGb EHQGgje Hf Sgd GdGTHjdj GdGSQGFjdj, CHh ESMGb,J (B649 (3g` s
(3ChdgG (B:s
(3MQa GdCda jhe JVGMc fhQg GdSQGA ddOgQ efg MdI SjQG s
(3BNQgG (B:s
(3de jHb ddgjeGf ChGge GdfjQGf bdJ UMjM s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B37s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(3 / 780) s
Keywords: (3GdCOHs